Possibilities of Weed Beet (Beta vulgaris, L. ssp. marritima) Regulation - Hnilicka, Roman; Pulkrabek, Josef; Pazderu, Katerina (Acta Agraria Debreceniensis, 2011)
Weed infestation regulation in sugar beet belongs to the most difficult growing measures, the aim of our work was to find out, if active substances contained in preparations Roundup and Fazor influence number, weight and germination of clusters in plants of weed beets. Statistically significant differences in germinability were found among control and all variants in which preparation Fazor was applied. The Roundup treatment did not have significant influence on germination. Presented results are only preliminary and one-year results, more experiments are necessary to determine the effects of the studied applications.